The Genus Metschnikowia in Enology - Vicente, Javier (Microorganisms, 2020)
Over the last decade, several non-Saccharomyces species have been used as an alternative yeast for producing wines with sensorial properties that are distinctive in comparison to those produced using only Saccharomyces cerevisiae as the classical inoculum. Among the non-Saccharomyces wine yeasts, Metschnikowia is one of the most investigated genera due to its widespread occurrence and its impact in winemaking, and it has been found in grapevine phyllospheres, fruit flies, grapes, and wine fermentations as being part of the resident microbiota of wineries and wine-making equipment. The versatility that allows some Metschnikowia species to be used for winemaking relies on an ability to grow in combination with other yeast species, such as S. cerevisiae, during the first stages of wine fermentation, thereby modulating the synthesis of secondary metabolites during fermentation in order to improve the sensory profile of the wine. Metschnikowia exerts a moderate fermentation power, some interesting enzymatic activities involving aromatic and color precursors, and potential antimicrobial activity against spoilage yeasts and fungi, resulting in this yeast being considered an interesting tool for use in the improvement of wine quality. The abovementioned properties have mostly been determined from studies on Metschnikowia pulcherrima wine strains. However, M. fructicola and M. viticola have also recently been studied for winemaking purposes.